Hubungan Kecanduan Bermain Game Online dengan Tingkat Prestasi Belajar Anak Kelas 9 SMP Islam Yayasan Pendidikan Saadatuddarin Tahun 2024 - Risma Novitasari; Inas Syabanasyah; Solehudin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Addiction is a feeling of wanting something very much trying to find what is being sought. Addiction to playing online games is an action of someone wanting to continue playing online games to spend uncontrollable time. The level of student learning achievement is the learning outcome achieved by students after making learning efforts and learning achievements after being assessed. The impact that influences addiction to playing online games is a decrease in learning achievement. The purpose of this study was to determine the relationship between addiction to playing online games and the level of learning achievement of grade 9 students of SMP Islam Yayasan Pendidikan Saadatuddarain. This type of research uses a quantitative method with a correlational analytical research type and cross-sectional design, the analysis test uses the Spearman Rank Test. The sampling used in this study was 70 grade 9 students of SMP Islam Yayasan Pendidikan Saadatuddarain students who were taken using the Total Sampling technique. The results of this study showed that 65 respondents (92.9%) were addicted to playing online games. The level of low learning achievement was 64 respondents (91.4%). The Spearman Rank test shows that the p value = 0.001, the correlation of the Spearman rank test coefficient value has a strong relationship level with a value of -0.708. Based on these results, it can be concluded that there is a relationship between addiction to playing online games and the level of learning achievement of 9th grade students of SMP Islam Yayasan Pendidikan Saadatuddarain.